2022
DOI: 10.1002/advs.202103029
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 Deficiency Promotes Pancreatic Cancer Immunogenicity by Activating the Cancer‐Autonomous DNA‐Sensing Signaling Axis

Abstract: Smad4, a key mediator of the transforming growth factor‐β signaling, is mutated or deleted in 20% of pancreatic ductal adenocarcinoma (PDAC) cancers and significantly affects cancer development. However, the effect of Smad4 loss on the immunogenicity and tumor immune microenvironment of PDAC is still unclear. Here, a surprising function of Smad4 in suppressing mouse PDAC tumor immunogenicity is identified. Although Smad4 deletion in tumor cells enhances proliferation in vitro, the in vivo growth of Smad4‐defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…However, there is currently no evidence to suggest that SMAD4 gene mutations are specifically associated with the response to tumour immunotherapy. Previous studies have shown that SMAD4 gene mutation can increase the immunogenicity of pancreatic cancer through the tumour's endogenous DNA sensing system 36 . Therefore, we propose a hypothesis that the low responsiveness of CCA with SMAD4 mutation to immunotherapy may be caused by the absence of its endogenous DNA sensing system.…”
Section: Discussionmentioning
confidence: 84%
“…However, there is currently no evidence to suggest that SMAD4 gene mutations are specifically associated with the response to tumour immunotherapy. Previous studies have shown that SMAD4 gene mutation can increase the immunogenicity of pancreatic cancer through the tumour's endogenous DNA sensing system 36 . Therefore, we propose a hypothesis that the low responsiveness of CCA with SMAD4 mutation to immunotherapy may be caused by the absence of its endogenous DNA sensing system.…”
Section: Discussionmentioning
confidence: 84%
“…Despite these analogical insights, other studies showed conflicting results. Recently, Xiong et al demonstrated that the absence of SMAD4 promotes tumor cell immunogenicity and may trigger activation of subsequent CD8 + T cells for tumor control ( 42 ). In addition, according to Li et al, SMAD4-depletion significantly augmented anti-tumor immunity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence data were obtained on a BD LSR Fortesa cell analyzer (BD Biosciences, Franklin Lakes, NJ) and analyzed using FlowJo Version 10. The number of cells counted by FCM analysis was divided by the weight of the tumor to obtain the number of cells per gram of tumor. …”
Section: Methodsmentioning
confidence: 99%